2017
DOI: 10.1021/acs.nanolett.7b03600
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Anisotropic Nanocomposite Hydrogels Direct in Situ Growth and Alignment of Myotubes

Abstract: While injectable in situ cross-linking hydrogels have attracted increasing attention as minimally invasive tissue scaffolds and controlled delivery systems, their inherently disorganized and isotropic network structure limits their utility in engineering oriented biological tissues. Traditional methods to prepare anisotropic hydrogels are not easily translatable to injectable systems given the need for external equipment to direct anisotropic gel fabrication and/or the required use of temperatures or solvents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 79 publications
2
111
0
Order By: Relevance
“…Alignment of pure CNC can be induced at relatively weak magnetic fields (>0.56 T) above the critical nanoparticle concentration required for nematic liquid crystals formation 36 . However, it has also been recently demonstrated that adsorption of polymers on CNC surface increases its effective volume fraction, leading to increased nematic structuring and therefore increased susceptibility to magnetic alignment 37,38 . These effects are hypothesized to enable the magnetic alignment of CNC at weaker magnetic fields and below the critical concentration required for nematic ordering, such as those explored in this work.…”
Section: Characterization Of Gelatin Nanocomposite Constructsmentioning
confidence: 99%
“…Alignment of pure CNC can be induced at relatively weak magnetic fields (>0.56 T) above the critical nanoparticle concentration required for nematic liquid crystals formation 36 . However, it has also been recently demonstrated that adsorption of polymers on CNC surface increases its effective volume fraction, leading to increased nematic structuring and therefore increased susceptibility to magnetic alignment 37,38 . These effects are hypothesized to enable the magnetic alignment of CNC at weaker magnetic fields and below the critical concentration required for nematic ordering, such as those explored in this work.…”
Section: Characterization Of Gelatin Nanocomposite Constructsmentioning
confidence: 99%
“…As reported by K.J. De France et al [ 29 ], the magnetic field-induced alignment of CNCs was successfully translated into a nanocomposite hydrogel based on hydrazone cross-linked poly(oligoethylene glycol methacrylate) (POEGMA) and physically incorporated CNCs after injection, which consequently endowed the hydrogel matrix with anisotropic properties. Meanwhile, the anisotropically mechanical property is directive for the motility and migration of cells, such as skeletal muscle myoblasts in the repair of muscle tissue.…”
Section: Cell–matrix Interactions and Delivery Of Bioactive Cues Imentioning
confidence: 91%
“…More interestingly, CNCs form a chiral nematic liquid crystal phase under the circumstance of controlling the ionic strength of suspension or applying a strong magnetic field [ 28 ]. Such features as extremely high stiffness of single nanorod (high crystallinity) and ordered alignment of CNCs in the liquid crystal phase make them attractive nanofillers in preparation of reinforced composite matrices with mechanically anisotropic features [ 29 ]. Meanwhile, the surface of CNCs is activated with carboxylates or sulfates, which result from and are dependent on the acidic process adopted.…”
Section: Nanocelluloses: Origin Preparation and Materials Propertmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue engineering (TE) scaffolds for anisotropic tissues have to satisfy the requirement of creating regional and directional anisotropy in three-dimensional space. To obtain this, the design and obtainment of patterns able to induce cell orientation along one preferential direction is needed, together with the enhancement of the mechanical properties in this direction (De France et al, 2017). The most used techniques to generate anisotropy in vitro are the use of mechanical force (Haque et al, 2010;Nardinocchi and Teresi, 2016), directional freezecasting (Chen et al, 2012;Bai et al, 2013) and micro-patterning (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%